Comparison of two simulation software for modelling a construction process - Wong, Kuan Yew (2011)
Construction process complexities lead to many difficulties imposed on construction planners and designers who are facing with different issues such as developing new methods or solving problems during a construction process. In order to solve these problems in construction industry, simulation can be an acceptable solution. In this regard, graphical methods have become a useful tool for process simulation. To do construction process simulation with a suitable graphical display, many simulation software are developed such as PROMODEL, SDESA, and etc. This paper aims at comparing two simulation tools (software), ARENA 13 and WITNESS 2004 Manufacturing Edition, for making a construction process simulation model. It shows that both software produce almost the same results and outputs for a given construction process. Also, the paper shows different kinds of features and reports provided by ARENA 13 and WITNESS 2004 Manufacturing Edition.